Exploring Al-‘Azl and Contemporary Contraceptive Practices: A Maqashid al-Shariah Perspective on Population Regulation and Reproductive Morality - Neng Nurcahyati Sinulingga; Endah Rundika Pratiw; Wildan Ansori Hasibuan; Hengki Wijaya (Pharos Journal of Theology, 2025)
This research seeks to examine contraceptive practices through the context of Maqashid a-Shariah (the objectives or higher intents of Islamic law) and illustrate the way Islamic principles are incorporated with current contraceptive practices. The need to harmonize religious and medical views in reproductive health policy is the urgency of this research, and this is especially so in the case of Muslims. This descriptive qualitative study uses a literature study and in-depth interviews with reproductive fiqh specialists as its research methods. The study shows that al-'Azl and other contraceptive techniques have existed in Islamic thought since early stage (dating back to the 7th century CE) and are invariably centered upon the protection and preservation of life and family and the maintenance of family unity and bloodlines. These findings authenticate the fact that contraceptive techniques reinforce both the well-being of the self and the community and are also in tandem with Maqashid al-Shariah to secure life and human dignity. This research proposes increasing intercultural and inter-faith dialogue to formulate a relatively comprehensive and ethical contraception policy. Reproductive health requires a comprehensive strategy in the world at large to ensure that the use of contraception is accepted as part and parcel of world ethics deliberations. This research will hopefully play an important role in enhancing the debate across religion and science to bring about more comprehensive and inclusive thinking about contraception with regard to world health policy in general.